Identification of Medicinal Plant Species in the Mount Puntang Area, Bandung Regency, West Java - Dharma, Yossi; Jayani, Faradila Mei; Hasibuan, Mhd Muhajir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Indonesia’s forest areas are rich in medicinal plant species that have been traditionally used by local communities; however, much of their potential remains undocumented and underutilized. Mount Puntang, Bandung Regency, West Java, is a mountainous forest area with high potential for medicinal plant diversity; however, scientific studies on the identification of species and the pharmacological potential of medicinal plants in this area remain limited. This study aims to identify medicinal plant species in the Mount Puntang area of Bandung Regency. The research was conducted in August 2020 utilizing a descriptive exploratory method. Primary data collection was carried out through fieldwork observations on individual plants in medicinal plant demonstration plots as well as in the home gardens of local residents surrounding the Mount Puntang forest area, supplemented by semi-structured interviews with 20 local informants. Data were analyzed quantitatively using descriptive statistics. The results showed the presence of 48 medicinal plant species from 29 families. The most dominant family was Acanthaceae, accounting for 10.42%, followed by Asteraceae, Fabaceae, Solanaceae, and Zingiberaceae, each accounting for 6.25%. The plant parts most frequently utilized were leaves (36.78%), roots (16.23%), stems (13.67%), fruits (10.26%), seeds (5.98%), flowers (5.13%), bark (4.27%), rhizomes (4.27%), and tubers (3.42%).